SEPARATION OF POWER: BERPISAH UNTUK BERTEMU - Sarip Sarip; Nur Rahman (Fakultas Hukum Universitas Muhammadiyah Cirebon, 2020)
Theorists struggle to determine the nature of the separation of power. There are many objections to the tripartite separation (three powers) of the state in the form of the legislature, executive and judiciary by referring to Montesquieu in his Spirit of the Laws for the history of political theory originating in the French state. The separation of powers is a vital feature of western democracies, enshrined in various federal and state constitutions. As a broad principle, theorists struggle to determine its precise nature, and many argue that the tripartite separation of state power into legislative, executive and judicial branches has proved simple and impossible. I think we should understand the separation of powers as a strategy used to structure the relationship between separate institutions. This structuring process empowers the creation of new relationships between institutions, with the aim of enhancing their institutional integrity. In short, we split up just to reconnect. These strategies direct attention to inter-agency relationships highlighting the contribution of these relationships to keeping institutional integrity together. Keywords: Separation of powers, Institutions, Authority, Meeting each other.